Isolation and identification of foodborne pathogens from seafood dishes - Jamari, Nurulain (2015)
Fooborne disease is not just a major international health problem but also give a negative impact on economic growth. This disease can be transmitted by consuming contaminated food with sufficient number of foodborne pathogens or ingesting its toxins. Poor hygiene practices during preparation of food is one of the crucial causes that lead to foodborne illness to occur. Seafood may be contaminated at source but this study focus on contamination of seafood dishes during preparation before consumption. In this study, two ready-to-eat seafood dishes were collected from different food stalls in Sri Serdang, Selangor. The samples were squid cooked with chili paste and cockles cooked with chili paste. The conventional cultural technique were used to analyze the food samples for foodborne pathogens. The number of bacterial counts in the food samples were counted using total viable count. The identification of bacterial isolates were done by conducting 13 biochemical tests. From a total of 22 isolates, six were detected as Enterobacter aerogenes and Alcaligenes faecalis, three isolates are Bacillus cereus and Corynebacterium xerosis, two are Klebsiella pneumoniae, and each one from Escherichia coli, Staphylococcus aureus, and Lactococcus lactis. From all of the identified bacteria, five of them are foodborne pathogens; Enterobacter aerogenes, B. cereus, K. pneumoniae, E. coli, and S. aureus.